Look Back to See What’s Ahead : A Review of Mega-PTAs on Services and Investment that Will Shape Future Trade Agreements - Molinuevo, Martín (World Bank, Washington, DC, 2020)
This paper draws the attention to the chapter on trade in services and investment of these agreements and their country-specific sets of commitments. This comprehensive approach is necessary as the disciplines in the text of the agreement set out the rights and obligations for the parties, but it is only the individual country commitments that reveal the sectoral scope and actual content of these PTAs. Not only do agreements differ in how countries approach basic provisions such as national treatment (NT), market access (MA), most favored nation (MFN) treatment and others (see Box 1 for more details) but the actual country commitments reveal whether countries have liberalized certain sectors, and to which extent. Therefore the focus of this analysis is on the services as well as the investment chapters and commitments of these selected five 'mega-PTAs'. Overall the purpose of this paper is to shade light on the critical aspects of the trade in services and investment chapters of the five selected mega-PTAs by highlighting the novelties and in particular by analyzing the annexed commitments (Annex one and two) of each agreement.